2003
DOI: 10.2166/wst.2003.0462
|View full text |Cite
|
Sign up to set email alerts
|

The microbial community analysis of a 5-stage BNR process with step feed system

Abstract: The microbial communities of 5-stage BNR activated sludge samples were analyzed using fluorescence in-situ hybridization (FISH) and 16S rDNA characterization. The total cell numbers of each reactor were from 2.36 x 10(9) cells/ml to 2.83 x 10(9) cells/ml. From 56.5% to 62.0% of total DAPI cell counts were hybridized to the most bacterial specific probe EUB 338. Among them, beta-proteobacteria were most dominant in each tank. The number of phosphate accumulating organisms (PAOs) was almost 50% of the total cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Lee et al, 2002;Liu et al, 2001;Mudaly et al, 2000). Actinobacteria also have been reported as the most dominant bacterial group in phosphorus-removing sludge (Christensson et al, 1998;H. W. Lee et al, 2003;T.…”
Section: Polyphosphate-accumulating Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, 2002;Liu et al, 2001;Mudaly et al, 2000). Actinobacteria also have been reported as the most dominant bacterial group in phosphorus-removing sludge (Christensson et al, 1998;H. W. Lee et al, 2003;T.…”
Section: Polyphosphate-accumulating Organismsmentioning
confidence: 99%
“…Gemmatimonas aurantiaca, a novel polyphosphate-accumulating isolate, placed in the new phylum Gemmatimonadetes, was retrieved from EBPR laboratory sludge (Zhang et al, 2003). Uncultured organisms belonging to the phylum Bacteroidetes, in the genus Flavobacteria and Cytophaga, have been identified repeatedly in substantial numbers with molecular techniques and DAPI staining in EBPR sludge samples (Dabert, Sialve, Delgenès, Moletta, and Godon, 2001;H. W. Lee, 2003).…”
Section: Polyphosphate-accumulating Organismsmentioning
confidence: 99%
“…36 Accession number AF388029). All the mentioned genera have been recovered from activated sludge by various authors (Lee et al 2003;Valle et al 2004). The Cytophaga-Flavobacterium group has been studied in relation to PHA production under anaerobic/aerobic conditions (Liu et al, 2001), while Candidatus Meganema perideroedes has been shown to be present and able to be stored in a aerobic reactor intermittently fed with acetate (Beccari et al, 1998; Levantesi et al, 2004).…”
Section: Microbial Characterizationmentioning
confidence: 99%
“…While some molecular data have suggested that the PAO populations active under anoxic and aerobic conditions might be different (Ahn et al, 2002;Lee et al, 2003), it seems increasingly likely that Accumulibacter are the major PAO populations in both denitrifying and conventional EBPR processes (Zeng et al, 2003;Kong et al, 2004;, emphasizing their metabolic versatility. Yet the story may be more complex than that.…”
mentioning
confidence: 99%